620.92 DETERMINING COMPARATIVE EFFICIENCY IN COMPOSITE FILM SOLAR DRYERS: Solar dryer - Muxtarov, Dilmurod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. For the development of mobile structures of solar drying devices, it is proposed to use a composite film developed on the basis of functional ceramics as a transparent wall. Determination of comparative efficiency in terms of drying speed of products in each device on the basis of experimental studies on drying of fruits and vegetables in drying devices. To provide suggestions, explanations and conclusions based on the conducted research. Methods. In the drying chamber, the conversion of solar radiation, i.e. exposure to the pulse to dehydrate the product to be dried by generating infrared rays. An empirical formula for determining the dynamics of drying in radiation drying devices has been developed. Results. Using the results of research conducted on drying devices, the comparative drying efficiency of devices for each product was determined. Conclusion. Based on the research conducted on the drying of apples, grapes, cherries, onions and carrots in drying devices, the comparative efficiency and drying speed of the Composite-1 film solar drying device were found to be 25% to 67% more efficient than the traditional film solar drying device. Also, in the final stage of drying of products, the differences in safe moisture content determined by each device are presented, and an empirical formula for determining the dynamics of drying in radiation drying devices and a methodology for its use are developed.